Evaluasi Perhitungan dan Pencatatan Pajak Penghasilan Pasal 22 atas Penjualan Barang pada CV ABC (Jurnal Riset Manajemen dan Akuntansi, 2025)
Compliance with tax obligations is a crucial aspect for business operators in conducting healthy and sustainable business activities, however in practice there are still business entities that pay insufficient attention to the importance of evaluating their tax obligations. This study aims to evaluate CV ABC calculation and recording of Article 22 Income Tax on sales transactions of goods to government agencies. This research uses a qualitative descriptive method. Data were collected through observation, documentation, and interviews with the parties handling the financial and tax reports of CV ABC. The research results show that CV ABC has accurately calculated Article 22 Income Tax in accordance with the specified regulations and that CV ABC has recorded Article 22 Income Tax sufficiently according to accounting standards.